Whole‐genome characterization of chronological age‐associated changes in methylome and circular RNAs in moso bamboo (Phyllostachys edulis) from vegetative to floral growth. (23rd March 2021) - Zhang, Zeyu; Wang, Huihui; Wang, Yongsheng; Xi, Feihu; Wang, Huiyuan; Kohnen, Markus V.; Gao, Pengfei; Wei, Wentao; Chen, Kai; Liu, Xuqing; Gao, Yubang; Han, Ximei; et al.
Summary: In mammals, DNA methylation is associated with aging. However, age‐related DNA methylation changes during phase transitions largely remain unstudied in plants. Moso bamboo ( Phyllostachys edulis ) requires a very long time to transition from the vegetative to the floral phase. To comprehensively investigate the association of DNA methylation with aging, we present here single‐base‐resolution DNA methylation profiles using both high‐throughput bisulfite sequencing and single‐molecule nanopore‐based DNA sequencing, covering the long period of vegetative growth and transition to flowering in moso bamboo. We discovered that CHH methylation gradually accumulates from vegetative to reproductive growth in a time‐dependent fashion. Differentially methylated regions, correlating with chronological aging, occurred preferentially at both transcription start sites and transcription termination sites. Genes with CG methylation changes showed an enrichment of Gene Ontology (GO) categories in 'vegetative to reproductive phase transition of meristem'. Combining methylation data with mRNA sequencing revealed that DNA methylation in promoters, introns and exons may have different roles in regulating gene expression. Finally, circular RNA (circRNA) sequencing revealed that the flanking introns of circRNAs are hypermethylated and enriched in long terminal repeat (LTR) retrotransposons. Together, the observations in this study provide insights into the dynamic DNA methylation and circRNA landscapes, correlating with chronological age, which paves the way to study further the impact of epigenetic factors on flowering in moso bamboo. Significance Statement: Moso bamboo requires a very long time to transition from the vegetative to the floral phase. Here, we found that the DNA methylation level varies with chronological age in moso bamboo. This study also provides insights into flanking introns of circRNAs, which are hypermethylated and enriched in LTR retrotransposons.